Retorno à ciclicidade ovariana e indução da ovulação em vacas Nelore utilizando eCG e GnRH - Barbosa, João Luiz (2017)
The objective of this study was to develop a protocol based on eCG, GnRH and PGF2α to induce resumption of cyclicity in anovular Nelore cows, for which two experiments were conducted. Experiment I aimed to determine the day interval between eCG injection and acquirement of ovulatory capacity and to estimate the percentage of cows that ovulated in response to GnRH injection. Experiment II was designed to determine the ovulation rate after the first and second injection of GnRH of cows that were submitted to a eCG-GnRH-PGFGnRH protocol. In Experiment 1 (n = 20), the percentage of cows that presented follicles with ovulatory capacity within two days after the administration of 800, 400, and 0 IU of eCG was 100%, 71.42%, and 66.66%, respectively. The ovulation rate after a single GnRH injection was 100%, 85.7%, and 66.66%, respectively; and there was no difference between eCG administration and none on the ovulation rate (P = 0,17). In Experiment 2, cows (n = 21) received 400 IU of eCG on Day 0, followed by GnRH (Day 2), PGF2α (Day 8) and GnRH (Day 10). The percentage of cows that responded to the first GnRH injection was higher than to the second, (71.42% vs. 19.04%, P < 0.001), considering that 23,8% of cows did not respond to any GnRH injection. Therefore, eCG is effective on inducing emergence of a new follicular wave within two days after its administration in anestrous Nelore cows; hence, it is effective to support the resumption of cyclicity. The protocols based on the administration of eCG, GnRH and PGF2α have been effective in inducing synchronized ovulation in the majority of cows after the first GnRH injection; however, not as effective after the second injection of GnRH. Consequently, additional studies are essential to enhance the efficiency of this protocol concerning the synchronized ovulation rate following the second GnRH injection.